2020
DOI: 10.3390/catal10020183
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Hydrogenation to Methanol over La2O3-Promoted CuO/ZnO/Al2O3 Catalysts: A Kinetic and Mechanistic Study

Abstract: The hydrogenation of CO2 to methanol has been investigated over CuO/ZnO/Al2O3 (CZA) catalysts, where a part of the Al2O3 (0, 25, 50, 75, or 100%) was substituted by La2O3. Results of catalytic performance tests obtained at atmospheric pressure showed that the addition of La2O3 generally resulted in a decrease of CO2 conversion and in an increase of methanol selectivity. Optimal results were obtained for the CZA-La50 catalyst, which exhibited a 30% higher yield of methanol, compared to the un-promoted sample. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Samson et al mentioned that the selection of the catalyst preparation method influences the physico-chemical properties such as the degree of Cu dispersion, electronic state, and polymorphism of ZrO 2 and concluded that the methanol formation rate accelerated by increasing the t-ZrO 2 phase in the Cu/ZrO 2 catalyst. 88 Kourtelesis et al 89 and Guo et al 90 have studied the significance of La 2 O 3 into CuO/ZnO/Al 2 O 3 and Cu/ZrO 2 catalysts. The inclusion of La 2 O 3 increases oxygen vacancies, enhances strong basic sites, and allows the formation of formate and methoxy species, which improve the CO 2 adsorption capacity and methanol yields.…”
Section: Cu-based Catalysts Studied For Methanol Synthesismentioning
confidence: 99%
“…Samson et al mentioned that the selection of the catalyst preparation method influences the physico-chemical properties such as the degree of Cu dispersion, electronic state, and polymorphism of ZrO 2 and concluded that the methanol formation rate accelerated by increasing the t-ZrO 2 phase in the Cu/ZrO 2 catalyst. 88 Kourtelesis et al 89 and Guo et al 90 have studied the significance of La 2 O 3 into CuO/ZnO/Al 2 O 3 and Cu/ZrO 2 catalysts. The inclusion of La 2 O 3 increases oxygen vacancies, enhances strong basic sites, and allows the formation of formate and methoxy species, which improve the CO 2 adsorption capacity and methanol yields.…”
Section: Cu-based Catalysts Studied For Methanol Synthesismentioning
confidence: 99%
“…The opposite effect of the different rare earth promotors on activity was mainly due to the enhanced synergistic effect and H 2 adsorption caused by the addition of La and Ce, which were not found in the catalysts with Pr and Nd as additives. Similarly, Kourtelesis et al 105 found that La 2 O 3 could promote 30% of the methanol yield for the CuO/ZnO/Al 2 O 3 catalyst. La 2 O 3 could be facilely introduced by a co-precipitation method, and the enhanced methanol yield could be attributed to enhanced adsorption of CO 2 and active intermediates.…”
Section: Co 2 Hydrogenation Reactionmentioning
confidence: 87%
“…Some groups used rare earth oxide as promotors to adjust the catalyst structure for CO 2 hydrogenation to methanol and obtained positive results. 104,105 For instance, Ban et al 104 verified that the using of La and Ce as promoters boosted the methanol production of CuZnZr catalyst, especially Ce. However, the introduction of Pr and Nd as additives decreased the activity.…”
Section: Co 2 Hydrogenation Reactionmentioning
confidence: 99%
“…Besides the conventional CuO/ZnO/Al 2 O 3 , different Cu-based catalytic systems have been investigated for the methanol synthesis from CO 2 [10][11][12][13]. Among them, the ZrO 2containing catalysts have been recently claimed to be very active and selective due to the versatile properties and weak hydrophilic character of zirconia [12].…”
Section: Introductionmentioning
confidence: 99%